Estratégias deliberadas em organizações de excelência reconhecida no Brasil - Acacia Branca Seco Ferreira (2004)
The study of the formulation and implementation of deliberate strategies is particularly important when are considered excellence organizations recognized in Brazil, above all when recent studies indicate that a great part of the companies in the Country is recognized significantly aparted of the best models and of the best administration practices. Three organizations that won the National Prize of the Quality - PNQ are analysis objects, in this study of multiple cases, being used Grounded Theory methodological procedures. In the search of understanding as the formulation processes and implementation of deliberate strategies happen, the members of those organizations were interviewed, in a simple observation, in a case, being the obtained data compared with documents organizacional and publications on the subject. The dimension of the analysis considered the present moment plus retrospective data, relative to the time of the obtaining of the Prize. The data revealed likeness, especially of foundations, in that it weighs, in some moments, there to be divergences of practices; they let to foresee possible associations among fall in the acting and negligence in the strategic administration. It is waited that the found results contribute to increase the knowledge on the administration of those companies recognized by your acting of " World " Class, motivating a deep reflexion of the subject.